An estimation of willingness to pay for secondary health care services in Tamil Nadu, India - Ramu, K (International Journal of Health, 2016)
The present study has estimated the willingness to pay (WTP) for secondary health care services (SHCS) in rural and urban environment of three districts in the state of Tamil Nadu during 2009-2011. Since the governments are struggling to mobilise additional financial Â Â Â Â resources to provide essential health care services to the deprived population in the country, assessing the WTP for utilising the public health care services are realised as very important at this juncture. In realizing the importance of augmentation of resources, it has been decided to introduce contingent valuation method (CVM) for WTP of SHCS. A disproportionate systematic random sampling method has been adopted for the selection of 720 households; representing 240 respondents from each of the three districts represent 120 from rural and 120 from urban. A major portion (92%) of the surveyed respondentsâ€™ gender was male, literacy was high (90%) and they belonged to productive age group. They generally involve themselves in the farm and non - farm activities and avail employment. Their per capita income is Rs.17871, and it is lower than the Indiaâ€™s PCI. The SHCS are classified into 26 categories as per the guidelines provided by public health medical officers in the state of Tamil Nadu. The different health care services started with entry fee to dental problem. The 98.6 per cent of the total surveyed respondents are ready to pay for SHCS in a public hospital and the remaining 2.4 per cent of them are not willing to pay for the same. The range of WTP for 26 SHCS is Rs. 2 - 7000; the range of mean value is Rs. 6 - 5008 and the range of SD is 2 - 2854. Considering the view of majority of the respondents, this study prescribes to introduce the range of user fee for the identified major public health care services. Since the range is differed significantly, it is suggested to follow the minimum amount initially and in a phased manner, the policy makers may prescribe to enhance the user fee after assessing the ground realities and loopholes. The estimated R2 value for SHCS is 20 per cent, which indicates that the selected 12 independent variables have low influence on WTP for SHCS. The study reports that the other exogenous factors like intensity of disease, accessibility of services, quality, urgency, need and perception are the predominant determinants of WTP for SHCS. The present research contends that constitution of district level co-ordination committee for fixing and implementing user fee for SHCS. Introduction of nominal fee (user fee) for SHCS may be fixed for affordable population, free services for BPL population and it would improve the efficiency and equity of the public health care services for the marginalised population. Finally, it is of utmost importance for health professionals to follow ethics in their profession.